2020
DOI: 10.1016/j.ssmph.2020.100623
|View full text |Cite|
|
Sign up to set email alerts
|

“Toxic” schools? How school exposures during adolescence influence trajectories of health through young adulthood

Abstract: A large body of research identifies the critical role of early-life social contexts such as neighborhoods and households in shaping life course trajectories of health. Less is known about whether and how school characteristics affect individual health and contribute to population health inequality. However, recent scholarship argues that some school environments are so stressful due to high levels of violence, disorder, and poverty that they may be “toxic” to student health, but this hypothesis has not been te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 66 publications
0
19
0
1
Order By: Relevance
“…However, emerging research in this field supports the extension of this model in adolescence [ 9 ]. In this regard, it has been found that violent environments can be toxic for adolescents and create health risks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, emerging research in this field supports the extension of this model in adolescence [ 9 ]. In this regard, it has been found that violent environments can be toxic for adolescents and create health risks [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together, these factors may lead to the elevated screen time burden experienced by youth from these communities. [21][22][23][24][25] Children from lower socio-economic backgrounds are more likely to have screens (e.g. television, video games) in their bedrooms and decreased accessibility to opportunities for physical activity or sport than those from higher socioeconomic backgrounds, and these factors jointly increase their daily screen time.…”
mentioning
confidence: 99%
“…A nationally representative study documented that disparities in physical activity levels among Hispanic and Black adolescents compared with White for the characteristics of the schools they attended, including racial composition and economic resources (23). These mechanisms are part of a broader constellation of differences in material and social characteristics across levels of school segregation (16,19,22,(26)(27)(28)30,42,43), including exposure to violence, a barrier to physical activity (29). Identifying place-based mechanisms linking school racial/ ethnic segregation to child obesity disparities is critical for the design of interventions to advance health equity beginning in childhood (18).…”
Section: Discussionmentioning
confidence: 99%